Evaluation of NID2 promoter methylation for screening of Oral squamous cell carcinoma - Ratakorn Srisuttee; Areeya Arayataweegool; Patnarin Mahattanasakul; Napadon Tangjaturonrasme; Virachai Kerekhanjanarong; Somboon Keelawat; Apiwat Mutirangura; Nakarin Kitkumthorn (My University, 2020)
Abstract Background Oral squamous cell carcinoma (OSCC) is an aggressive human malignancy. Because of late diagnosis and recurrence of OSCC, the treatment of patients with OSCC is often ineffective. Thus, finding novel biomarkers of OSCC are essential. Here we derived a methylation marker by utilizing methylation microarray data and testing its capacity in cross-sectional study designed for OSCC detection and screening. Methods According to bioinformatics analysis of total of 27,578 cg sites, cg22881914 of Nidogen 2 ( NID2 ) methylation was selected for evaluation. Next, we confirmed the methylation status by bisulfite sequencing from the microdissected OSCC cells in comparison with the microdissected oral epithelia. Subsequently, we developed a simple technique using real-time PCR with the specific probe to examine the ability for the detection of OSCC in the oral epithelial samples, which included 103 oral rinse and 82 oral swab samples. Results Based on the comparison of microdissected tissue, cg22881914 of NID2 was proved to be methylated in most OSCC cells but unmethylated in the normal oral epithelia. Furthermore, the methylated NID2 -relied quantitative PCR approach has demonstrated that this marker assists in distinguishing among patients with OSCC from normal oral epithelia, smokers, and patients with oral lichen planus using the non-invasive oral rinse and swab samples. Conclusions Specific methylation at cg22881914 of NID2 of OSCC could be used as an important potential marker for detecting OSCC. Thus, to certify the utility of this marker, further studies with a larger sample size are needed.
Keywords: Bisulfite sequencing; Surgical oncology; Epigenetics and DNA Methylation